2015
DOI: 10.1155/2015/391767
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofLactobacillus plantarumStrain K21 on High-Fat Diet-Fed Obese Mice

Abstract: Recent studies have demonstrated beneficial effects of specific probiotics on alleviating obesity-related disorders. Here we aimed to identify probiotics with potential antiobesity activity among 88 lactic acid bacterial strains via in vitro screening assays, and a Lactobacillus plantarum strain K21 was found to harbor abilities required for hydrolyzing bile salt, reducing cholesterol, and inhibiting the accumulation of lipid in 3T3-L1 preadipocytes. Furthermore, effects of K21 on diet-induced obese (DIO) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 39 publications
5
52
1
Order By: Relevance
“…The normalizing effects of probiotic administration on serum lipid profiles is through inhibition of lipogenesis. These findings were consistent with those of Wu et al [33], who found that L. plantarum K21, as a probiotic, produced cholesterol-lowering and bile salt-hydrolyzing capacities.…”
Section: Discussionsupporting
confidence: 93%
“…The normalizing effects of probiotic administration on serum lipid profiles is through inhibition of lipogenesis. These findings were consistent with those of Wu et al [33], who found that L. plantarum K21, as a probiotic, produced cholesterol-lowering and bile salt-hydrolyzing capacities.…”
Section: Discussionsupporting
confidence: 93%
“…Because the microbiota is rapidly altered by diet and the consumption of a HFD is known to cause obesity , it has been suggested that diet‐induced alterations in microbiota could contribute to the pathogenesis of obesity. To identify potentially beneficial and detrimental bacteria for obesity development, we review the HFD‐induced effects on common parameters related to obesity and on the rodent microbiota . A number of significant correlations between the human or rodent microbiota and several common parameters related to obesity have been reported (Table ) .…”
Section: Intestinal Microbiota Composition Associated With Diet‐inducmentioning
confidence: 99%
“…Both Bifidobacterium spp. and A. muciniphila are correlated to decreased serum leptin levels in DIO mice (Table 1) (54), while the administration of either Bifidobacterium strains or A. muciniphila (but also B. uniformis CECT 7771) ameliorated the elevated serum leptin levels in HFD-fed mice (41,43,49,55). Additionally, HFD-induced leptin resistance was improved by a single prebiotic treatment that increased the relative abundance of Bifidobacterium spp.…”
Section: Leptin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, L. plantarum strain K21 that inhibits lipid accumulation in 3T3-L1 preadipocytes, alleviated body weight gain and epididymal fat mass accumulation, reduced plasma leptin levels, decreased cholesterol and triglyceride levels as well as mitigated liver damage in a mouse model of diet-induced obesity. 289 Antilipidemic effects of lactobacilli were also evaluated along with memory-enhancing activity in aged Fischer 344 rats. 290 A probiotic mixture of L. plantarum KY1032 and L. curvatus HY7601 was provided once a day for 8 weeks.…”
Section: Other Pathologiesmentioning
confidence: 99%